Impact of aortic stenting on peripheral vascular function and daytime systolic blood pressure in adult coarctation. Issue 7 (8th August 2007) - Chen, S S M; Donald, A E; Storry, C; Halcox, J P; Bonhoeffer, P; Deanfield, J E
Abstract : Objectives: To determine the relation of ambulatory systolic blood pressure to aortic obstruction and more extensive vascular dysfunction, assessed by central aortic, peripheral conduit arterial and resistance vessel function. Methods: 12 adults (5 native, 7 recoarctation) were studied before, and 2 weeks and 6 months after aortic stenting. Systolic blood pressure was measured during normal daily living by 24-hour ambulatory monitoring. Central aortic function was assessed by pulse wave analysis (augmentation index). Brachial artery flow-mediated dilatation and dilatation in response to 25 μg of sublingual glyceryl trinitrate was assessed by ultrasound to measure peripheral conduit arterial and resistance vessel function. Baseline vascular measures were compared with those of 12 matched controls. Results: Patients had a higher augmentation index, impaired endothelium-dependent and -independent dilatation, and forearm vascular resistance (p<0.02). After successful gradient relief by stenting, daytime ambulatory systolic blood pressure (151 (134, 166) mm Hg vs 138 (130, 150) mm Hg, p = 0.01) and the augmentation index (26 (15, 34) vs 23 (13, 30), p = 0.03) fell progressively over 6 months, but did not completely normalise. Endothelium-dependent and -independent dilatation, and forearm vascular resistance remained unchanged and impaired. Conclusion: Relief of aortic obstruction is associated with improvement in central aortic function and results in reduction of daytime ambulatory systolic blood pressure. Peripheral vascular dysfunction, however, remains unchanged and may contribute to residual hypertension.